Pengaruh Perencanaan Pajak, Penghindaran Pajak, dan Profitabilitas terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Mila Apriani; Martini Martini (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to determine the effect of tax planning, tax avoidance, and profitability on firm value. The population in this research is mining sector companies listed on the Indonesia Stock Exchange in financial reports for the 2019-2023 period. The sampling technique in this research used a purposive sampling method and a sample of 58 companies was obtained. The analysis technique used is multiple linear regression analysis using SPSS version 22 software. The results of this research show that profitability has a positive effect on firm value and tax planning and tax avoidance have a negative effect on firm value.